Effect of different income housing zones on effluent quality of Biofil toilet waste digesters in Accra, Ghana - Philip Amoah; Eric G. Nartey; Alyse Schrecongost (2016)
This study was carried out to assess the effect of different income-housing zones on the quality of effluent from standard Biofil® toilet waste digesters in Accra, Ghana. Records of the digesters installed were obtained from BiofilCom and were sorted out into income-housing zones (low, middle and high income housing zones). In all, 36 toilet digesters were found accessible and sampled 3 times each for effluent. Samples were analyzed for E. coli, Total coliform, helminth eggs, BOD, TSS, NH3-N and PO4-P, using standard methods. Results show that effluent quality exceeded the requirements set by Ghana EPA for discharge into water bodies. However, high removal efficiencies were obtained for BOD (84%) and TSS (82%). In most cases, the pollutant concentrations were significantly higher in effluents from the high-income zones than in the middle and low income zones.